Defining tetrahydrobiopterin responsiveness in phenylketonuria: survey results from 38 countries - Evers, Roeland A. F.; van Wegberg, A. M. J.; Ahring, K.; Beblo, S.; Bélanger-Quintana, A.; Bosch, A. M.; Burlina, A.; Campistol, J.; Coskun, T.; Feillet, F.; Giżewska, M.; Huijbregts, S. C. J.; et al. (Molecular genetics and metabolism, 2021)
Background - A subset of patients with phenylketonuria benefit from treatment with tetrahydrobiopterin (BH4), although there is no consensus on the definition of BH4 responsiveness. The aim of this study therefore was to gain insight into the definitions of long-term BH4 responsiveness being used around the world. - Methods - We performed a web-based survey targeting healthcare professionals involved in the treatment of PKU patients. Data were analysed according to geographical region (Europe, USA/Canada, other). - Results - We analysed 166 responses. Long-term BH4 responsiveness was commonly defined using natural protein tolerance (95.6%), improvement of metabolic control (73.5%) and increase in quality of life (48.2%). When a specific value for a reduction in phenylalanine concentrations was reported (n = 89), 30% and 20% were most frequently used as cut-off values (76% and 19% of respondents, respectively). When a specific relative increase in natural protein tolerance was used to define long-term BH4 responsiveness (n = 71), respondents most commonly reported cut-off values of 30% and 100% (28% of respondents in both cases). Respondents from USA/Canada (n = 50) generally used less strict cut-off values compared to Europe (n = 96). Furthermore, respondents working within the same center answered differently. - Conclusion - The results of this study suggest a very heterogeneous situation on the topic of defining long-term BH4 responsiveness, not only at a worldwide level but also within centers. Developing a strong evidence- and consensus-based definition would improve the quality of BH4 treatment.